Consumer standards as a strategic device to mitigate ratchet effects in dynamic regulation - Raffaele Fiocco; Roland Strausz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Strategic delegation to an independent regulator with a pure consumer standard improves dynamic regulation by mitigating ratchet effects associated with short term contracting. A consumer standard alleviates the regulator's myopic temptation to raise output after learning the firm is inefficient. Anticipating this tougher regulatory behavior, efficient firms find cost exaggeration less attractive. This reduces the need for long term rents and mitigates ratchet effects. The regulator's welfare standard biased towards consumers comes, however, at the cost of some allocative distortion from the genuine social welfare perspective. Hence, a trade-off results which favors strategic delegation when efficient firms are relatively likely.
Keywords: D82; L51; 330; Dynamic regulation; strategic delegation; consumer standard; ratchet effect; limited commitment; Regulierung; Verbraucherschutz; Unternehmensregulierung; Wirtschaftliche Effizienz; Theorie